CRITERIA FOR ASSESSING THE ECONOMIC EFFICIENCY OF THE APPLICATION OF GROWTH STIMULANTS, MICRO FERTILIZERS AND MINERAL FERTILIZERS ON SOYBEAN CROPS IN THE CONDITIONS OF THE SOUTH OF KAZAKHSTAN - Yerkuatov, R. N.; Sydyк, D. A.; Kenenbaev, S. B.; Kazybayeva, A. T. (Жангир хана, 2023)
The article presents the results of using the effectiveness of growth stimulants, micro-fertilizers and herbicides on soybean crops. We have calculated all types of costs associated with the purchase and delivery of fertilizers, herbicides and their applications during the growing season of plants. Economic calculations were carried out according to the prevailing market norms and rates in the wage system for 2021 in the LLP «South-Western Research Institute of Animal Husbandry and Plant Growing» and in the southern region of Kazakhstan as a whole. Over the years of the experiments, the highest indicators of conditional net income of the «Swallow» variety have reached - 503.0 thousand tenge/ha with a reduction in the cost of seeds to 11.6 thousand. tenge/ts were provided on the 5th variant of the experiment, where, against the background of seed treatment with the growth stimulator «vimpel» - 0.5 l/t + micronutrient «Oracle» - 1.5 l/t during the growing season of soybean plants in the phase of 3-5 leaves and during budding, the crops were twice treated with the above-mentioned growth stimulator «vimpel» - 0.5 l/ha, micronutrient «Oracle»multicomplex - 2.0 l/ha + micronutrient «Oracle»molybdenumcolofermin – 0.5 l/ha using herbicides according to the scheme of experiments. The best indicators of the efficiency of soybean cultivation were revealed with the treatment of seeds of the Zhansaya variety with nitragine and the introduction of phosphorus fertilizers P60 kg/ha and the treatment of crops with the growth stimulant «Vimpel»-0.5 l/ha, micro-fertilization «оracle»multicomplex at 2.0 l/ha and micro-fertilization «оracle» molybdenum colofermin – 0.5 l/ha. conditional net income amounted to 533.1 thousand tenge/ha with a reduction in the cost of seeds – 12.1 thousand tenge/ts against the background of herbicidal treatment.
Yerkuatov, R. N. CRITERIA FOR ASSESSING THE ECONOMIC EFFICIENCY OF THE APPLICATION OF GROWTH STIMULANTS, MICRO FERTILIZERS AND MINERAL FERTILIZERS ON SOYBEAN CROPS IN THE CONDITIONS OF THE SOUTH OF KAZAKHSTAN / R. N. Yerkuatov, D. A. Sydyк, S. B. Kenenbaev , A. T. Kazybayeva. - Текст : непосредственный // Ғылым және білім=Наука и образование=Science and education. - 2023. - № 3-2 (72). Ч. ІІ. - Р. 160-172. - ISSN 2305-9397
Keywords: soybean; growth stimulant; micronutrients; mineral fertilizers; nitrogine; herbicide; economic efficiency; бобовые культуры; зкату; научной издание